Rites of passage how today's Jews celebrate, commemorate, and commiserate - Greenspoon, Leonard J. (Leonard Jay) (Studies in Jewish civilization, 2010)
Scholars tend to call them "rites of passage." Most people prefer to speak of them as life-cycle events or milestones. Jews like to speak of simchas, when there's something (a birth, bar or bat mitzvah, or a wedding) to celebrate. These are key moments for individuals and for the families and communities of which they are a part. This volume offers new insights into rituals as old as the Hebrew Bible and as new as the twenty-first century in contexts as familiar as the American Midwest and as exotic as Karaism. This collection examines and frequently affirms some of the rituals that have traditionally been associated with these events, while inviting readers to cast a critical eye on the ways in which these customs have developed in recent years. The authors, who include congregational leaders as well as scholars, also affirm the need to expand or enhance existing ceremonies to include groups whose needs have not traditionally been addressed.